2020
DOI: 10.1017/s0007114520002706
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous vegetable intake is inversely associated with extensive abdominal aortic calcification in elderly women: a cross-sectional study

Abstract: We have previously shown higher intake of cruciferous vegetables is inversely associated with carotid artery intima-media thickness. To further test the hypothesis that an increased consumption of cruciferous vegetables is associated with reduced indicators of structural vascular disease in other areas of the vascular tree, we aimed to investigate the cross-sectional association between cruciferous vegetable intake and extensive calcification in the abdominal aorta. Dietary intake was assessed, using a food fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…13 We have also seen cruciferous vegetables, another contributor to flavonoid intake, associates with lower odds of extensive AAC in this cohort. 14 In our current analysis of the PLSAW cohort, we build upon our prior research, finding higher black tea intake also associates with lower AAC. This finding is in agreement with several cohort studies reporting higher black tea consumption associates with lower calcifications of the coronary artery, 16,17 and abdominal aorta.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…13 We have also seen cruciferous vegetables, another contributor to flavonoid intake, associates with lower odds of extensive AAC in this cohort. 14 In our current analysis of the PLSAW cohort, we build upon our prior research, finding higher black tea intake also associates with lower AAC. This finding is in agreement with several cohort studies reporting higher black tea consumption associates with lower calcifications of the coronary artery, 16,17 and abdominal aorta.…”
Section: Discussionmentioning
confidence: 94%
“…13 We have also seen cruciferous vegetables, another contributor to flavonoid intake, associates with lower odds of extensive AAC in this cohort. 14 In our current analysis of the PLSAW cohort, we build upon our prior research, finding higher black tea intake also associates with lower Odds ratios are comparing the specific level of food or beverage intake (horizontal axis) to those with zero consumption set as the reference point for analyses of black tea, chocolate and fruit juice, and in the analysis of red wine, modest consumers were set as the reference group, to account for abstainer bias. 26 Horizontal axes are truncated at 2 SDs above the exposure means for visualization purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study analyzed the relationships between some food groups and AAC, and found that apple intake was an independent protective factor for AAC in older women, each additional 50 g/day apple intake resulted in a 24% lower OR of severe AAC [17]. A study found that cruciferous vegetable intake was negatively correlated with AAC [18]. Other studies have reported the effects of dietary nutritional intake, such as magnesium and zinc, on coronary artery calcification and AAC [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…"Potato, roasted and fried, including hot chips" was excluded as these are not considered part of a healthy diet. This method of classifying vegetable types has been used extensively [35][36][37][38]. Intake for each FV type was calculated (g/day) and subsequently categorised into quartiles.…”
Section: Fruit and Vegetable Typesmentioning
confidence: 99%